Ponta Grossa and Castro zones in Paraná talc district, Brazil, ore properties and mineral industry - GONDIM, ANTONIO CARLOS (Boletim Paranaense de Geociências, 2002)
Talc deposits of Paraná district occur as layers, lenses, veins and irregular bodies. The country rocks are dolomite marbles of the late proterozoic Itaiacoca Group. The talc ores are generally in situ, formed by metamorphic and hydrothermal processes, but there are some deposits that present concentrations of alloctone materials. These materials are partially remobilized by carstic dissolution and/or by colluvionar transport. Talc ores differ due their chemical composition, morphology, associated minerals, whiteness and some other properties. The talc minerals in the district of Paraná can be unctuous and not unctuous, platy and powdery, sparry and micro-crystalline and some form massive and disseminated ore deposits. The Southern zone or Ponta Grossa zone exhibits a talc ore more lamellar, platy, unctuous, softness and more varied associated minerals than the ore situated in Northern zone or Castro zone in which the talc is more powder in natural way. There is one deposit in the São José mine that belongs to the Ponta Grossa zone, that is an exception comparing with the other deposits in terms of its presented characteristics. The parameters that govern the specific nature of each commercial talc grade as well as its use in industrial applications including the polypropylene manufacturing are discussed in this paper.